B and T Lymphocyte Attenuator Tempers Early Infection Immunity - Sun, Yonglian (2009)
Co-inhibitory pathways are thought to act in later stages of an adaptive immune response, but whether co-inhibition contributes to early innate immunity is unclear. We show that engagement of the newly discovered co-inhibitory receptor B and T lymphocyte attenuator (BTLA) by herpesvirus entry mediator (HVEM) is critical for negatively regulating early host immunity against intracellular bacteria. Both HVEM(-/-) and BTLA(-/-), but not LIGHT(-/-), mice are more resistant to listeriosis compared to wild type mice, and blockade of the BTLA pathway promotes, while engagement inhibits, early bacterial clearance. Differences in bacterial clearance were seen as early as 1 day post-infection, implicating the initial innate response. Therefore, innate cell function in BTLA(-/-) mice was studied. We show that innate cells from BTLA(-/-) mice secrete significantly more pro-inflammatory cytokines upon stimulation with heat-killed listeria. These results provide the first evidence that a co-inhibitory pathway plays a critical role in regulating early host innate immunity against infection.